Novel empowered supports for iron-based Fischer-Tropsch in a power-to-liquids process - Ketlogetswe, Oaitse (Department of Chemical Engineering, 2024)
Fischer-Tropsch (FT) synthesis is a process that converts carbon monoxide and hydrogen into liquid hydrocarbons 1 . In the past, FT synthesis has been used to produce gasoline and diesel from coal and natural gas. However, with increasing demand for renewable and sustainable energy sources, there has been renewed interest in using FT to produce clean fuels 2 . The FT synthesis process takes place in the presence of a catalyst, at moderate temperatures and pressures. Iron-based catalysts are frequently used in commercial FT as they are quite useful in hydrogen lean synthesis gas because of their high water-gas shift activity. Nevertheless, these catalysts often need to be promoted to optimize their performance and they are prone to deactivation under FT conditions 3 . Promotion with potassium is often done to shift the FT performance and selectivities, while manganese and copper are often added to stir catalyst reduction 4 . Potassium is often used to modify iron-based catalysts to improve their performance. It has been suggested that potassium can impact the rate at which carbon is formed during FT by facilitating CO dissociation on the catalyst surface. Potassium also inhibits hydrogen chemisorption resulting in more carbon on the catalyst surface, longer chain products and higher olefin production 4,5 . The large ionic radius of potassium, however, has been reported to prevent its incorporation into iron oxide during synthesis, resulting in its mobility at the catalyst surface. The potassium mobility during FT results in enrichment of carbon on the catalyst surface and consequently catalyst deactivation 6 . In this study, we explored the possibility of using perovskites materials as support structures for the iron catalyst, and potassium incorporated within their structures. The perovskites allowed for better dispersion of the catalysts and improved control over the contact between the iron catalyst and potassium promoter. This in turn suppressed the movement of the promoter species, leading to improved catalytic performance. Two lanthanum-based perovskites were examined: LaAlO3-δ and LaTiO3-δ. The LaAlO3-δ catalysts were modified by substituting potassium to the A site and substituting 20 atom-% manganese to the B site. A range of materials with varying amounts of potassium, La1- xKxAl0.8Mn0.2O3-δ, (x = 0, 2, 4, 6, 8, 10 atom-%) were prepared via the citrate method 7 . The LaTiO3-δ catalysts were only modified by substituting potassium on the A site. A series of potassium substituted La1- xKxTiO3-δ perovskites (x = 0, 5, 10, 15, 20 and 30 atom-%) were prepared using a wet chemical technique 8 . Iron nanoparticles prepared using the coprecipitation method 9 , were deposited onto these supports as catalyst for FT synthesis process. The effect of potassium promotion on the properties and performance of these catalysts were evaluated. These catalysts were activated under H2 flow at 80 ml/min at 450 °C for 15 hours. Fischer-Tropsch synthesis was conducted in a 600 ml continuously stirred reactor tank at 240 °C, 15 bar with synthesis gas ratio of 2 (H2/CO = 2) and a space velocity of 2.4L/(h.gcatalyst). The catalysts performance was evaluated over a 48-hour period using online GC-TCD and offline GC-FID. In this study, the Fe-La1-xKxAl0.8Mn0.2O3-δ catalysts with potassium promotion showed higher catalytic activity than the unpromoted catalyst. The activity of the catalysts increased with increasing potassium loading until a maximum was reached at 8 atom-% potassium loading. The higher activity of the potassium promoted catalysts was attributed to the enhanced formation of iron carbide phases, which have been shown to be active in FT synthesis. Potassium promotion also led to lower methane selectivity, which was not dependent on the amount of potassium added. The results were ascribed to the water-gas shift activity of the iron catalyst. There was also a decrease in selectivity of C2 – C4 hydrocarbons and increased selectivity of C5+ hydrocarbons, while reducing the selectivity of oxygenates. Potassium promotion on the Fe-La1-xKxTiO3-δ catalysts resulted in structural change from orthorhombic at low potassium promotion to cubic structures at higher potassium promotion. The in situ XRD results revealed that potassium results in reduced onset reduction temperature from Fe3O4 to wüstite (FeO) and retards the reduction process from the FeO to metallic Fe. Nonetheless, it enhanced the initial formation of carbides through its influence on CO and H2 chemisorption. There was improved catalytic activity of the catalysts until a maximum at 10 atom-% potassium loading. On the other hand, this promotion led to a decrease in methane selectivity over time. The water-gas shift activity was higher on the promoted catalysts with no clear trend on the effect of amount of potassium added. Furthermore, potassium promotion resulted in a decrease in the selectivity of C2 – C4 hydrocarbons, slight increase in C5+ hydrocarbons selectivity and little impact on the productivity of the oxygenates. These developed catalysts had shown stability under FT reaction conditions as there was no observed structural change after FT synthesis. Due to their demonstrated stability at higher temperatures, these materials may be suitable for use in other catalytic processes such as reverse water-gas-shift reaction. Additionally, the lanthanum titanate perovskites could be promoted with manganese to investigate their reducibility and potentially improve their performance.